2023
DOI: 10.1021/acs.langmuir.2c02861
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Adsorption of β-Glucosidase onto Wrinkled SiO2 Nanoparticles To Boost the Yield of Immobilization of an Efficient Biocatalyst

Abstract: β-Glucosidase (BG) catalyzes the hydrolysis of cellobiose to glucose, a substrate for fermentation to produce the carbon-neutral fuel bioethanol. Enzyme thermal stability and reusability can be improved through immobilization onto insoluble supports. Moreover, nanoscaled matrixes allow for preserving high reaction rates. In this work, BG was physically immobilized onto wrinkled SiO 2 nanoparticles (WSNs). The adsorption procedure was tuned by varying the BG:WSNs weight ratio to achieve the maximum controllabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Nevertheless, the free enzyme was completely inactivated after 4 h of incubation at 60 • C. This result clearly displays the efficiency of the immobilization method to protect enzymes against heat inactivation. Other studies [34,35] confirm the improved thermal stability of the immobilized enzyme compared to the soluble enzyme.…”
Section: Thermal Stability Of Plc Bc Immobilized On Different Supportsmentioning
confidence: 67%
“…Nevertheless, the free enzyme was completely inactivated after 4 h of incubation at 60 • C. This result clearly displays the efficiency of the immobilization method to protect enzymes against heat inactivation. Other studies [34,35] confirm the improved thermal stability of the immobilized enzyme compared to the soluble enzyme.…”
Section: Thermal Stability Of Plc Bc Immobilized On Different Supportsmentioning
confidence: 67%
“…In a previous study by Sanchez-Ramirez et al [ 45 ], it was shown that cellulase immobilized on chitosan-magnetic nanoparticles retained 50 % of its activity after 4 h at temperatures of 60 °C and 70 °C. Similarly, Pota et al [ 46 ] demonstrated that β-glucosidase immobilized on wrinkled SiO 2 nanoparticles exhibited slightly enhanced stability when incubated at 70 °C. Furthermore, Wan et al [ 47 ] showed that β-glucosidase immobilized on a Fe 3 O 4 @POP composite displayed improved thermal stability at 70 °C.…”
Section: Resultsmentioning
confidence: 95%
“…The immobilized enzyme exhibited a km value of 13.4 mM, which was higher than that of the free β-glucosidase (km = 6.98 mM). In general, immobilization may increase enzyme resistance to the substrate and, as a result, raise the km value because immobilization restricted access to the enzyme active site [ 46 ]. Califano et al [ 53 ] and Verma et al [ 54 ] highlighted the potential influence of diffusion limitations on the km observed for the immobilized enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation